Efficacy and Safety of Initial Combination Treatment of an Alpha Blocker with an Anticholinergic Medication in Benign Prostatic Hyperplasia Patients with Lower Urinary Tract Symptoms: Updated Meta-Analysis. - Hyun Jung Kim; Hwa Yeon Sun; Hoon Choi; Jae Young Park; Jae Hyun Bae; Seung Whan Doo; Won Jae Yang; Yun Seob Song; Young Myoung Ko; Jae Heon Kim (PLoS ONE)
Background There is still controversy as to whether initial combination treatment is superior to serial addition of anticholinergics after maintenance or induction of alpha blockers in benign prostatic hyperplasia (BPH)/lower urinary tract symptoms (LUTS). Objective The objective of this study was to determine the benefits and safety of initial combination treatment of an alpha blocker with anticholinergic medication in BPH/LUTS through a systematic review and meta-analysis. Methods We conducted a meta-analysis of improvement in LUTS using International Prostate Symptom Score (IPSS), maximal urinary flow rate (Qmax), post-voided residual volume (PVR), and quality of life (QoL). Results In total, 16 studies were included in our analysis, with a total sample size of 3,548 subjects (2,195 experimental subjects and 1,353 controls). The mean change in total IPSS improvement from baseline in the combination group versus the alpha blocker monotherapy group was -0.03 (95% CI: -0.14-0.08). The pooled overall SMD change of storage IPSS improvement from baseline was -0.28 (95% CI: -0.40 - -0.17). The pooled overall SMD changes of QoL, Qmax, and PVR were -0.29 (95% CI: -0.50 - -0.07), 0.00 (95% CI: -0.08-0.08), and 0.56 (95% CI: 0.23-0.89), respectively. There was no significant difference in the number of acute urinary retention (AUR) events or PVR. Conclusions Initial combination treatment of an alpha blocker with anticholinergic medication is efficacious for in BPH/ LUTS with improved measures such as storage symptoms and QoL without causing significant deterioration of voiding function.